Noisiness of the video amplifier made by the cascode circuit with dynamic load; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 4 : Power engineering - Maslennikov V. N. (Power engineering, 2007)
Заглавие с титульного листа